Long-term sleep apnea CPAP via tracheostomy in children with tracheomalacia: 20-year experience - Sriboonyong, Tidarat; Preutthipan, Aroonwan; Nugboon, Malinee (Frontiers in Pediatrics, 2023)
Introduction: Children with severe tracheobronchomalacia may need placements of tracheostomies and long-term mechanical ventilation. Due to financial constraints, continuous positive airway pressure (CPAP) machines commonly used to treat obstructive sleep apnea in adults have been utilized to deliver positive distending pressure to such children at our institution for more than 20 years with favorable outcomes. We, therefore, reported our experience with 15 children using this machine. Methods: This is a retrospective study during 2001-2021. Results: Fifteen children, 9 boys, aged ranged 3 months – 5.6 years, were discharged home with CPAP via tracheostomies. All had co-morbidities including gastroesophageal reflux (n=9, 60%), neuromuscular disorders (n=6, 40%), genetic abnormalities (n=6, 40%), cardiac diseases (n=4, 27%) and chronic lungs (n=3, 20%). Eight (53%) children were aged less than 1 year old. The smallest child was aged 3 months old, weighing 4.9 Kg. All caregivers were relatives and non-medical health professionals. The 1-month and 1-year readmission rates were 13% and 66% respectively. No factor-associated unfavorable outcomes were statistically identified. No complications related to CPAP malfunction were found. Five (33%) were weaned off CPAP, and 3 died (2 from sepsis and 1 from a sudden unknown cause). Conclusion: We first reported the use of sleep apnea CPAP via tracheostomy in children with severe tracheomalacia. In limited-resource countries, this simple device may be another option for long-term invasive ventilatory support.